INOVASI TATA KELOLA SAMPAH ORGANIK UNTUK MENDUKUNG PARIWISATA BERKELANJUTAN PADA DESTINASI WISATA DANAU LUT TAWAR, ACEH TENGAH - Nurliana Nurliana; Ayu Rahma Nengsi; Rahmahidayati Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
This study examines the challenges and opportunities in managing organic waste to support sustainable tourism at Lake Lut Tawar, Aceh Tengah. Organic waste has become a critical environmental issue in this tourist destination due to limited infrastructure, low public awareness, and inconsistent government support. Using a qualitative approach, data were collected through in-depth interviews, questionnaires, field observations, and focus group discussions involving local communities, tourism managers, government representatives, and visitors. The findings reveal four dominant challenges: low awareness of waste separation among residents and tourists, inadequate waste management infrastructure such as the absence of segregated bins and processing facilities, minimal community participation in waste management programs, and limited budget allocation and operational consistency from local authorities. However, the study also identifies significant opportunities for innovation, particularly the adoption of simple composting technologies and environmental education initiatives targeting local schools and communities. Community members showed strong interest in participating in training activities related to composting and waste reduction when supported with adequate facilities and guidance. The study concludes that sustainable organic waste management at Lake Lut Tawar requires collaborative efforts involving communities, tourism stakeholders, and government institutions. Strengthening infrastructure, enhancing environmental education, and implementing community-based composting systems can become strategic pathways toward sustainable tourism and improved environmental quality in the region.